Chitosan for Removal of Mercury from Water - NAIR, K. G RAMACHANDRAN; MADHAVAN, P (Fishery Technology, 2017)
Chitosan from prawn waste was used for the removal of mercury from solutions. Mercuric chloride solutions containing 250, 500, 1000, 10000 and 1,00,000 ng of Hg+2/ ml were treated with chitosan samples of different particle size for different periods. The effect of initial concentration of mercury in the solution, particle size of chitosan andtime of treatment on the adsorption of Hg+ 3 were studied. The residual mercury content after treatment for ten min. with chitosan of 40 mesh size from a solution of initialconcentration 10,000 ng/ml was 10 ngfrnl whereas it was 50 ng/ml for chitosan of largerparticle size (10-20 mesh). From solutions of lower concentrations complete removalof mercury was possible by chitosan treatment. Though the particle size and time oftreatment have significant effect, the concentration of mercury in solution is more influentialon the removal of mercury from solution.